2020
DOI: 10.1080/16583655.2020.1713570
|View full text |Cite
|
Sign up to set email alerts
|

Effect of RF plasma on Moringa seeds germination and growth

Abstract: The paper presents the effect of cold plasma (RF-Ar low-pressure plasma) on Moringa oleifera seeds. Five groups of seeds characterized by the different exposure times (1, 5, 10 and 15 mints) as well as untreated seeds. The highest germination parameters were obtained for seeds treated for the exposure times of 1 min. Analysis of the data showed a statistically significant impact of RF plasma on the seeds germination parameters. The surface properties of the plasma-treated samples are examined using scanning el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
0
11
0
1
Order By: Relevance
“…Low-pressure RF plasma processes are successfully utilized to improve the germination of various seeds like Moringa oleifera seeds. Their exposure to an RF plasma of argon during 1 minute at 100 W and 2 Torr allows the increase in their germination by 20% and the subsequent shoot growth by more than 30 % [12]. Complementarily with these results, it has been shown that plasma can favor the diffusion of mineral elements in the coat of Quinoa seeds exposed to a capacitive RF reactor at 0.1 mbar, resulting in higher germination rate [13].…”
Section: I2 Dry Atmospheric Plasma Priming (Dapp)mentioning
confidence: 71%
“…Low-pressure RF plasma processes are successfully utilized to improve the germination of various seeds like Moringa oleifera seeds. Their exposure to an RF plasma of argon during 1 minute at 100 W and 2 Torr allows the increase in their germination by 20% and the subsequent shoot growth by more than 30 % [12]. Complementarily with these results, it has been shown that plasma can favor the diffusion of mineral elements in the coat of Quinoa seeds exposed to a capacitive RF reactor at 0.1 mbar, resulting in higher germination rate [13].…”
Section: I2 Dry Atmospheric Plasma Priming (Dapp)mentioning
confidence: 71%
“…Changes in germination or plant growth parameters have been observed with all the gases listed above. For example, helium was used in References [30,35,36,68,78,82,84,94], argon in References [22,23,33,38,60,62,109,111,117,128,133], air in References [11,36,41,48,51,58,61,79,80,90], and nitrogen in References [9,30,61,69,85,95,99] Various gases [24,118] or mixtures of gases are used in References [50,77,86,92] while nitrogen or oxygen [88,120] is used as a carrier gas in References [13,64]. Evidently, the reactive species composition differs for different ratios of oxygen and nitrogen, as shown by Tomekova et al …”
Section: Gas Type Flow Rate and Pressurementioning
confidence: 99%
“…[143] Plant exposure to too high an intensity negatively affects the growth results. [144] Studies using Morgina, [117] black gram, [41] or wheat [39,95] seeds use dark conditions and this again may be due to the seed type. Almost all other studies use short or long day cycles, which are less stressful for the plant than continuous light, even though the results would be obtained sooner.…”
Section: Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no significant variations in the mass loss were found across plasma exposure times of 2 and 3 min. The etching of the seed surface by plasma treatment may be responsible for the reduction in mass of the treated carrot in this case [28,56].…”
Section: Estimation Of Mass Loss Due To Plasma Treatmentmentioning
confidence: 99%